The United Arab Emirates: Some lessons in economic development - Yaw Nyarko (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
Oil was discovered in the United Arab Emirates (UAE) just 50 years ago. During that time, UAE has been able to transform itself into a rapidly modernizing country, which is fast becoming a major economic hub and a key player on the international economic landscape. This paper discusses a number of aspects of the development strategy of the UAE that contributed to its phenomenal development: (i) the political system, which has resulted in a perception of stability and minimal political risk, encouraging investment; (ii) oil; (iii) development strategies that have resulted in a very dynamic business environment; (iv) open importation of foreign skills and management; (v) labour policies that have enabled the immigration of vast numbers of foreign lower-skilled workers. There are, of course, also concerns for the future, and indeed each of the five positive attributes listed above has a flip side which is a potential major challenge for the future.
Keywords: O53; 330; role models; United Arab Emirates; success; Erdölförderung; Sozialer Wandel; Entwicklung; Wirtschaftspolitik; Wirtschaftspolitisches Ziel; Saudi-Arabien